Synthesis And Characterization Of pH-Sensitive Polyelectrolyte Nanogels For Oral Delivery Of Bovine Serum Albumin And Insulin As Model Proteins - Mudassir, Jahanzeb (2018)
Peptide and protein are administered parentrally owing to their instability and insufficient bioavailability through oral route. Parenteral administration is associated with poor patient compliance due to pain and discomfort by multiple injections. Oral administration can be beneficial to improve patient compliance and physiologic response to peptide and protein (e.g. insulin). The aim of the present study was to synthesize pH sensitive polyelectrolyte methyl methacrylate/itaconic acid (MMA/IA) nanogels to be used as a carrier for oral delivery of model proteins (BSA and insulin).